Job satisfaction, work environment and intent to stay of Jordanian midwives. (28th July 2020) - Alnuaimi, K.; Ali, R.; Al‐Younis, N.
Abstract : Aim: The aims of this study were to (1) assess the levels of Jordanian midwives' job satisfaction, intention to stay and work environment; (2) examine the relationship between work environment and intention to stay, and the level of job satisfaction among midwives working in Jordanian hospitals and maternal and child health centres and (3) to investigate the associations between job satisfaction and selected demographic variables among Jordanian midwives. Background: The shortage, turnover and retention of midwives are global problems and Jordan is one of the countries thathas a shortage of midwifery workforce. Job satisfaction is well studied among nurses worldwide; however, there are inadequate studies that have assessed the job satisfaction among midwives including Jordan. Methods: A descriptive, correlational design survey was used and a sample of 413 midwives were recruited from 14 different hospital settings (12 governmental and 2 teaching hospitals) and 8 health centres. Results: The levels of job satisfaction of Jordanian midwives were neither satisfied nor unsatisfied. The overall mean intent to stay at work was between neutral to agree in general. A positive significant correlation was found between job satisfaction, work environment and intent to stay. The work environment was neither a favourable nor an unfavourable. Conclusion and implications for nursing, health and education policy: Jordanian midwives have neutral job satisfaction and work environment. Managerial plans and interventions are needed to improve midwives' job satisfaction and to create a favourable work environment which might reflect positively on their work and performance and improve their retention. Policymakers and mangers should enhance midwives' job satisfaction through external reward via salary, vacation and benefits packages. Engaging in research activities, publication and more collaboration with academic staff may improve midwives' professional development. Midwives should take more active roles in hospital affairs and receive more support by their management in Jordan.